Promoting Culinary Heritages as a Destination Attraction: A Case Study of Ancient Temple Food ‘Mahaaprasaada’ - Debasis Sahoo (International Journal of Religious Tourism and Pilgrimage, 2020)
The growth of the food tourism segment in the last two decades has opened enormous scope for the marketing & promotion of ‘indigenous food products’ which otherwise remain limited to a particular region. These unique culinary products have created special segments like food & wine tourism, oleo tourism, whiskey tourism, beer tourism, and religious food tourism (like Halal & Kosher tourism). From this perspective ‘religious culinary heritage’ (practiced in ancient Hindu temples) shows a huge potential to be marketed as a tourism attraction, however, there are very few studies about this topic. Hence the present research identifies and analyses the unique heritage aspects (Eno-gastronomic elements) of an ancient Hindu temple food - ‘Mahaaprasaada’ (as practiced at Jagannath Temple Puri, India) and its potential as a destination attraction. Initially the Eno-gastronomic aspects of Mahaaprasaada were identified & interpreted through ‘Directed Qualitative Content Analysis.’ This required the review of temple literature, developing a questionnaire for personal in-depth interviews and focus group discussions (with temple officials, cooking staff & priests), field visits (to the temple premises & associated areas), observation (covert, overt & participatory) of the ongoing cooking and distribution mechanisms and recording data through event, time and instantaneous sampling methods. Post interpretation, the ethnicity and Eno-gastronomic nature of the culinary heritage (Mahaaprasaada) was analysed through Actor Network Theory. From the current research it can be generalised that religious gastronomic practices followed by the heritage temples of India, possess a huge number of ‘Eno-gastronomic elements’ that are highly influenced by the cultural traditions of the place. Moreover, the awareness level of tourists about these aspects varies with their demographic profile such as nationality, gender, education, state, age etc. Despite some limitations which are outlined in the paper, this research shows great potential and promising scope for religious food tourism.